Iraq : A Political History - Dawisha, A. I. (Book collections on Project MUSE., 2013)
With each day that passed after the 2003 invasion, the United States seemed to sink deeper in the treacherous quicksand of Iraq's social discord, floundering in the face of deep ethno-sectarian divisions that have impeded the creation of a viable state and the molding of a unified Iraqi identity. Yet as this book shows in this superb political history, the story of a fragile and socially fractured Iraq did not begin with the American-led invasion--it is as old as Iraq itself. The book traces the history of the Iraqi state from its inception in 1921 following the collapse of the Ottoman Empire and up to the present day.